Physicochemical characterisation, immunogenicity and protective efficacy of a lead streptococcal vaccine: progress towards Phase I trial. Issue 1 (December 2017) - Pandey, Manisha; Powell, Jessica; Calcutt, Ainslie; Zaman, Mehfuz; Phillips, Zachary; Ho, Mei; Batzloff, Michael; Good, Michael
Abstract Globally, group A streptococcal infections are responsible for over 500, 000 deaths per year. A safe vaccine that does not induce autoimmune pathology and that affords coverage for most GAS serotypes is highly desired. We have previously demonstrated that a vaccine based on the conserved M-protein epitope, J8 was safe and immunogenic in a pilot Phase I study. We subsequently improved vaccine efficacy by incorporation of a B-cell epitope from the IL-8 protease, SpyCEP, which protected IL-8 and enhanced neutrophil ingress to the site of infection. We have now substituted the carrier protein, diphtheria toxoid with its superior analogue, CRM197 which provides better immunogenicity and is widely used in licenced human vaccines. The new vaccine was compared with the DT conjugate vaccine to confirm that these modifications have not altered the physicochemical properties of the vaccine. This vaccine, when tested in an animal model of GAS infection, demonstrated significant reduction in systemic and local GAS burden, with comparable efficacy to the DT conjugate vaccine. The vaccine was shown to be equally effective in the presence of human plasma and in the presence of pre-existing DT-specific antibodies, thus minimising concerns regarding its potential efficacy in humans.